Spectrum of Changes in Gastric Mucosa with Helicobacter Pylori Infection - Ghimire, PG; Ghimire, P; Goel, RG; Bahl, DV (Journal of Nepalgunj Medical College, 2015)
Aim: To evaluate the spectrum of mucosal changes in endoscopy guided gastric biopsies and analyze the association of Helicobacter pylori with demographic factors. Materials and Methods: It was a cross sectional analytical study conducted in the Department of Pathology during the period from December 2011 to April 2012. A total of 52 endoscopic biopsy specimens, each fulfilling the inclusive criteria were selected and processed using standard histopathological technique and stained with Haematoxylin-Eosin stain and modified Giemsa stain for Helicobacter pylori. Histopathological, ultrasonographic and endoscopic findings were correlated. Data were analyzed using SPSS 17. Results: Out of 52 cases enrolled in our study, 29 (55.8%) were males and 23 (44.2%) were females with a male: female ratio of 1.2:1. H. pylori infection was present in 16 (30.8 %) of biopsies and was significantly greater in the younger age group between 21 to 40 years (p value <0.024). Histopathological examination showed atrophy of the gastric mucosa in 18 (34.6%) cases, dysplasia in one and intestinal metaplasia in three cases. Statistically significant relation (p value < 0.006) was seen between H. pylori and mucosal atrophy. No significant association was seen between gender and presence of H. pylori in the gastric mucosa (p value < 0.16). Conclusions: Histopathological study of endoscopic biopsy showed spectrum of changes in symptomatic cases. H pylori was seen significantly in younger age with atrophy of gastric mucosa as a significant finding. Journal of Nepalgunj Medical College Vol.12(1) 2014: 29-31